Arguments in University-Level Debating: Subjective or Objective - Ignasia Yuyun; Siegfrieda Mursita Putri (Journal of Language and Literature, 2016)
This article reports a study on subjectivity and objectivity of arguments in university-level debating. This study aims to identify the level of subjectivity and objectivity of arguments in debating. Employing mainly a qualitative method focusing on discourse, the study took a recorded 2015 National University Debating Championship in Kopertis 3 Jakarta with British Parliamentary debating system as the source of data. Hallidayans modality analysis was the basis of the analysis. The use of orientation and manifestation of modality and modality metaphor were analyzed to reveal the level of subjectivity and objectivity among debaters in university-level debating. At last, the study shows the dominant use of explicit subjective modality in delivering arguments. This tendency implies that debaters prominently express their points of view to the debate.